2015
DOI: 10.1139/apnm-2014-0556
|View full text |Cite
|
Sign up to set email alerts
|

Coenzyme Q10 supplementation downregulates the increase of monocytes expressing toll-like receptor 4 in response to 6-day intensive training in kendo athletes

Abstract: This study examined changes in toll-like receptor 4 (TLR-4)-expressing monocytes and lymphocyte subpopulations in response to continuous intensive exercise training in athletes, as well as the effect of coenzyme Q10 (CoQ10) supplementation on these changes. Eighteen male elite kendo athletes in Japan were randomly assigned to a CoQ10-supplementation group (n = 9) or a placebo-supplementation group (n = 9) using a double-blind method. Subjects in the CoQ10 group took 300 mg CoQ10 per day for 20 days. Subjects i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…Herein, pretreatment with CoQ10 combined with AES significantly reduced the expression of TLR4, MyD88, and NF-κB-p65 compared to each drug used alone. Our results are in line with previous reports [Rimmon et al, 2013;Cheng et al, 2015;Shimizu et al, 2015]. This superior effect of the combination therapy indicates that CoQ10 and AES worked together to block the TLR4/MyD88/NF-κB signaling pathway and consequently decreased the activation of NLRP-3 inflammasome and pyroptosis.…”
Section: Discussionsupporting
confidence: 93%
“…Herein, pretreatment with CoQ10 combined with AES significantly reduced the expression of TLR4, MyD88, and NF-κB-p65 compared to each drug used alone. Our results are in line with previous reports [Rimmon et al, 2013;Cheng et al, 2015;Shimizu et al, 2015]. This superior effect of the combination therapy indicates that CoQ10 and AES worked together to block the TLR4/MyD88/NF-κB signaling pathway and consequently decreased the activation of NLRP-3 inflammasome and pyroptosis.…”
Section: Discussionsupporting
confidence: 93%
“…Over the last decade, a growing body of data has supported the potential clinical use of dietary CoQ10 supplementation in health and chronic illnesses [ 13 , 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a double-blind 2-weeks long clinical trial carried out on 18 male elite kendo athletes demonstrated that 300 mg/day of CoQ 10 contributed to down-regulate the expression of Toll-like receptor 4 (TLR4), considered as an event downstream the ROS production and responsible for immune system regulation. Therefore, in athletes undergoing intensive exercise, continuous CoQ 10 supplementation is recommended 14 weeks before starting the training in order to inhibit exercise-induced inflammation and immune deficiency [ 64 ].…”
Section: Resultsmentioning
confidence: 99%